2015
DOI: 10.1194/jlr.d059725
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lipopolysaccharide analysis using HPLC/MS/MS and its combination with the limulus amebocyte lysate assay

Abstract: Systemic infl ammatory response syndrome (SIRS) is defi ned by a cluster of clinical signs that include tachycardia, leukocytosis, tachypnoea, and pyrexia ( 1 ). Although SIRS is a major consequence of sepsis (i.e., a deleterious, nonresolving infl ammatory response to infection that can lead to multiple organ dysfunction and septic shock), it can be caused by many pathological events that are not associated with the bacterial infection ( 1 ). It is of major importance to distinguish between noninfectious SIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 43 publications
3
108
0
2
Order By: Relevance
“…The FDA guidelines have received some criticism due to the fact, for example, that it is not easy to elute LPS from the test item. One study showed that only 40–70% of inoculated LPS was recovered from devices following a very stringent extraction protocol in ethanol …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA guidelines have received some criticism due to the fact, for example, that it is not easy to elute LPS from the test item. One study showed that only 40–70% of inoculated LPS was recovered from devices following a very stringent extraction protocol in ethanol …”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the authors used only small implants, due to the extremely costly LAL assay reagents. Lipscomb et al tested 260 surgical instruments, from nine primary care units, and used 4,6‐diamidino‐2‐phenylindole dihydrochloride to detect LPS and proteinaceous contaminations. Their results were negative for LPS, but 60% showed a high degree of protein soiling (0.4–4.2 μg protein/mm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a wide variety of mass spectrometry (MS)-based techniques has been applied for the detection of complex LPS or lipid A [2730]. For example, Caroff et al reported direct micro-extraction and analysis of intact LPS by combined thin-layer chromatography and matrix-assisted laser desorption ionization (MALDI) MS [27].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, other approaches for the measurement of LPS using MS are to fractionate intact LPS, extract specific fatty acids and derivatize them prior to analysis. Gas chromatography (GC)- or liquid chromatography (LC) coupled to MS is then applied for the separation, detection and quantitation of targeted fatty acid [3032]. These methods can also be applied to carbohydrate-containing samples, which normally interfere with endotoxin biological assays but still suffer from multiple sample pre-treatment steps and tedious, time-consuming method development.…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly used in metabolic studies and therefore was adapted to the plasma of different species to this aim (Laugerette et al, 2015). Of note, emerging methods aim at quantifying LPS molecules via the analysis of 3-hydroxymuristic acid from their lipid A in plasma (Pais de Barros et al, 2015).…”
Section: Endotoxins Are Proinflammatory Moleculesmentioning
confidence: 99%